The Effectiveness of GTM Plus on Students' English b - Nur Laila Molla (Universitas Pancasakti Tegal, 2014)
Grammar Translation Method (GTM) is one of teaching methods. The writerdiscovered a new model of GTM, later called GTM Plus. This research will provewhether this method completely effective to students’ achievement. Severalexperiments are taken to two difference classes. The experiments were held at JuniorHigh School 1 Tegal. There were two sample classes consisting of twenty twostudents for each, one as experimental class and the other as control class.Experimental class was taught with GTM Plus and the other class without. Therewere pre-test and post-test for both classes. A true experimental research was held.Test and observation conducted, the writer calculated test validity, reliability,difficulty level and discriminating power. The Sample of students was takenrandomly. The test is analyzed and calculated using nonparametric statistic. Theresult proves 21.6% increasing students’ achievement. The pre-test mean of controlgroup is 6.11 and 6.72 for post-test while the pre-test mean of experimental group is7.07 and 8.56 for post-test. Percentage of score improvement is 21.1%. This meansthat the implementation of Grammar Translation Method GTM) Plus gives positiveeffect to students’ achievement on English reading tests and also speaking ability.The results show that mean of experimental group is higher than of control group.This gives positive effect on the implementation of Grammar Translation Method(GTM) Plus at school widely. Analyzing feedback through questionnaire ofexperimental group also shows 86% acceptance of this teaching method.